Synchrotron radiation from drifting magnetoplasma - Shukla P.K.; Singh R.P.; Singh K.P.; Singh R.N. (My University, 2025)
The effects of the drift motion of the plasma on the radiated synchrotron power are studied in detail with special reference to the mognetospheric nnd solar coronal plasmas. It is shown that the radiated power is enhanced in the presence of the drifting plasma. © 1974 Taylor & Francis Group, LLC.